Management of Social Media by Public Relations of Kebumen Police Resort in Maintaining the Image of Kebumen Police Resort - Muhammad Iqbal Sholahuddin; Riski Damastuti (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
In mid-July, the Indonesian National Police was hit by a case that became an extraordinary that caused POLRI to be highlighted by the public at that time. This was due to the many irregularities in the case that was sticking out. Then three months later, another case involving a police general emerged, causing the police to be hit by an extraordinarily large case in one year, which attracted the attention of the public, foreigners and even the President of the Republic of Indonesia. The impact of the two cases above is a decrease in trust and image of the police in the eyes of the Indonesian people. Therefore, the National Police Chief through the police public relations division, which at that time was at the forefront of increasing public trust and the image of the police in the community, optimized digital media management and several programs which could lift the image of the police in the eyes of the community, this was also done by the units under him, one of which was the public relations section of Kebumen Police, at this time Kebumen Police had managed several digital media such as Instagram, Facebook, Twitter and also TikTok, according to digital media monitoring by Kebumen Police public relations members, the image of Kebumen Police had improved again